Feline leishmaniosis with focus on ocular manifestation: a case report - Ingo Schäfer; Albert Schmidt; Fritz Gräßer; Andrea Schieszler; Heike Aupperle-Lellbach; Gerhard Loesenbeck; Michaela Gentil; Elisabeth Müller; Torsten J. Naucke (Parasites & Vectors, 2023)
Abstract Background In Europe, feline leishmaniosis is commonly caused by Leishmania infantum. There is little knowledge regarding pathogenesis, ocular manifestations and long-term follow-ups in cats with leishmaniosis. Findings A 6-year-old female, spayed European Shorthair cat was imported from Spain to Germany 2 years prior to its first clinical presentation. The cat showed lethargy, weight loss, ulcerative lesions on the front limbs and high-grade chronic uveitis. The diagnosis of L. infantum infection was based on the cytological finding of amastigotes in skin lesions, positive qPCR of EDTA-blood and positive PCR of a cyto-brush sample from the conjunctiva. Supportive findings included positive serology by IFAT, serum protein capillary electrophoresis with peaks in alpha2- and gamma-globulin sections and marked elevation of SAA. Enucleation had to be performed on day 288 on both eyes because of blindness, glaucoma and high-grade uveitis. Histologically, high numbers of Leishmania spp. amastigotes were found in histiocytes. IFAT and PCR were positive in the aqueous humor in both eyes, respectively. Feline leukemia virus antigen and feline immunodeficiency virus antibody testings were positive. Hematological and biochemical results revealed mild leukocytosis with lymphocytosis, monocytosis and eosinopenia as well as marked elevation of SAA and hyperglobulinemia. The cat was treated with allopurinol, responded well and was still alive at follow-up on day 288 after first presentation. However, enucleation was necessary because of refractory glaucoma and uveitis.  Conclusion For the first time, ocular evidence of Leishmania IgG antibodies was demonstrated in the aqueous humor of both eyes in cats. There is limited knowledge about the pathogenesis, treatment options and outcomes in cats infected with L. infantum. This case report supports the hypothesis that immunosuppression increases the risk of clinical signs of leishmaniasis in cats. Alpha2- and gamma-globulin peaks in serum protein capillary electrophoresis are supportive criteria for the diagnosis of L. infantum infection. SAA is valuable for monitoring. Regarding ophthalmology, uveitis and glaucoma may have a poor prognosis.  Graphical abstract